Scaling laws in the evolutionary processes of marine animals over the last 540 million years - Haitao Shang (Geosystems and Geoenvironment, 2024)
Scaling laws are ubiquitous in modern biological systems. However, whether such patterns existed in deep-time biological systems is less investigated; the best-known example is the scaling law between the frequency and size of extinction events. Here, I show that the variation rates of biodiversity, origination intensity, extinction intensity, and body size of marine animals during the last 540 million years exhibited scaling laws. I then derive a general form of these scaling laws from a conceptual model with some principles of thermodynamics and assumptions about the global biological system. The results in this study suggest that the scaling laws systematically appearing in the biological metrics characterizing different aspects of the evolutionary processes of marine animals likely belong to the same universality class and probably derived from a set of common factors.